Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Adverse childhood experiences, adult adiposity, and risk of young-onset breast cancer subtypes in a population-based case-control study - Lydia Marcus Post; Young Ik Cho; James Topitzes; DPhuong Do; Dorothy R. Pathak; Ann S. Hamilton; Amani M. Nuru-Jeter; Kelly A. Hirko; Jamila L. Kwarteng; Richard Houang; Ann G. Schwartz; Ellen M. Velie (Cancer Causes & Control, 2026)
Purpose Adverse childhood experiences (ACEs) are hypothesized to increase breast cancer risk via social and physiological pathways, yet associations between ACEs and young-onset breast cancer (BC) subtypes–and potential mediators (e.g., adiposity) of these associations–are largely unstudied. We sought to evaluate associations between ACEs and young-onset BC molecular subtypes, and the potential mediating effects of adiposity, in a population-based case–control study of invasive young-onset BC. Methods Cases (n = 1,754) were identified from the Los Angeles County and Metropolitan Detroit SEER registries, 2010–2015, and area-based, frequency-matched controls (n = 1,350) sampled from the 2010 Census. Associations between ACEs aged < 18 years and young-onset BC (diagnosed ages 20 to < 50 years), overall and by subtype (luminal A, luminal B, HER2 + , triple negative [TN]), were examined using weighted logistic regression. Adult adiposity (i.e., body mass index 12 months before diagnosis, waist circumference at interview) was evaluated as a mediator of these associations using weighted path analyses. Results ACEs (≥ 1 vs 0) were not significantly associated with young-onset BC (all p trend > 0.10); however, reporting one ACE (vs 0) was associated with TN (odds ratio [OR] = 1.85 [95% confidence interval [95%CI] = 1.08–3.16]). For individual ACEs, death of a loved one (vs 0 ACEs) was associated with HER2 + (OR = 2.50 [95%CI = 1.06–5.88]) and potentially TN (OR = 1.72 [95%CI = 0.96–3.10]) young-onset BC; other associations were non-significant. In path analyses, ACEs had a significant total effect on luminal A (β = 0.08, p = 0.03) and TN (β = 0.13, p < 0.01) tumors, with adiposity mitigating this association for luminal A tumors (β = -0.01, p = 0.04; TN β = 0.00, p > 0.05). Conclusions Bereavement during childhood was associated with higher odds of HER2 + young-onset BC, and there was some evidence of an association between ACEs and other young-onset BC subtypes, particularly TN.

NPF-induced CCN enhancement over an urban location in Eastern Himalayan Foothills: A campaign-based study - Barlin Das; Binita Pathak; Uday Bhattacharjee; Partha Jyoti Sahu; Arundhati Kundu; Arup Borgohain; Mukunda M. Gogoi; Shyam S. Kundu; Kalyan Bhuyan; Pradip K. Bhuyan (Atmospheric Environment, 2025)

In situ evaluation of genotoxicity and cytotoxicity associated with microplastics in an intertidal clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Shubra Singh; Prem Kumar; Martin Xavier; Saurav Kumar; Nalini Poojary; Madhuri S. Pathak; Kiran D. Rasal; Gajanan S. Ghode; Naresh S. Nagpure (Marine Pollution Bulletin, 2025)

An economical and rapid method of comet assay and micronucleus cytome assay for genotoxicity biomonitoring using clam, Gafrarium divaricatum (Gmelin, 1791) - M. Harshavarthini; Edward Inpent Campal; Shubra Singh; Nalini Poojary; Martin Xavier; Kiran D. Rasal; Madhuri S. Pathak; Naresh S. Nagpure (DNA Repair, 2025)

Integration of Mycorrhizae, Azotobacter and Pseudomonas spp (PSB) with NPK and their Effects on Sugarcane Crop and Soil Health in Uttar Pradesh, India - M. K. Tripathi; S. K. Shukla; V. P. Jaiswal; Lalan Sharma; Mona Nagargade; A. D. Pathak; A. P. Dwivedi; Ankur Tripathi; V. K. Singh; V. P. Singh; Ajay Ranka (Sugar Tech, 2025)

Modified emission and scaling factors for methane and nitrous oxide in rice system of India: A country specific disaggregate approach - Pratap Bhattacharyya; A. Bhatia; N. Jain; D. Chatterjee; S. Mohanty; M. Prabhakar; Pratibha M; N.N. Jambhulkar; S. Ananthakrishnan; S.K. Nayak; A.K. Nayak; H. Pathak (Journal of Environmental Management, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Exploring the toxicity of chromium on aquatic ecosystems: a comprehensive assessment of growth, physiological responses, genotoxicity, and histological alterations in Etroplus suratensis (Bloch, 1790) juveniles - Ramya V.; Madhuri S. Pathak; Kapil Sukhdhane; Kishore Kumar Krishnani; Thongam Ibemcha Chanu; Harini G.; Harshavarthini M. (Aquaculture International, 2024)

Genetic Profiling of Spodoptera litura (Noctuidae: Lepidoptera) in Indian Sub-Tropical Sugar Beet - Santeshwari Srivastava; Varucha Misra; Arun Baitha; Himanshu Pandey; S. N. Sushil; M. Mohan; A. D. Pathak; Sangeeta Srivastava; Dinesh Singh; Ashutosh Kumar Mall (Sugar Tech, 2024)

Inclusion of organic and inorganic extractive species improves growth, survival and physiological responses of GIFT fish reared in freshwater integrated multi-trophic aquaculture system - S.V. Shinde; K.S. Sukhdhane; K.K. Krishnani; B. Rani A. M.; M.S. Pathak; T.I. Chanu; S. Munilkumar (Aquaculture, 2024)

Lifetime alcohol consumption patterns and young-onset breast cancer by subtype among Non-Hispanic Black and White women in the Young Women’s Health History Study - Kelly A. Hirko; Darek R. Lucas; Dorothy R. Pathak; Ann S. Hamilton; Lydia M. Post; Ugonna Ihenacho; Nicole Bohme Carnegie; Richard T. Houang; Kendra Schwartz; Ellen M. Velie (Cancer Causes & Control, 2024)

Space based Earth observation approach for exploring hydrocarbon prospects in an intracratonic rift basin – A study in north Cambay basin, Gujarat - Arindam Guha; Nikhil Kumar Baranval; Ashish Misra; Swati Singh; M. Shivashankar; Santosh Garain; Subhobroto Mazumder; S. Pathak; K. Vinod Kumar (Advances in Space Research, 2023)

Enhancing Crop Productivity and Profitability of Autumn Sugarcane with Intercropping of Winter Vegetables in Real Farming Situations of North-Central India - S. N. Singh; Chandra Gupta; V. K. Singh; A. D. Pathak; A. K. Sah; M. K. Tripathi; Sanjiv Gupta; J. R. Patnaik (Sugar Tech, 2023)

Thyroid hormone dynamics of Tharparkar and Sahiwal cattle during induced heat stress - Anjali; Gururaj VK; Lipika Sarma; M. Tripathi; Med Ram Verma; Vinay Verma; M. C. Pathak; H. A. Samad; V. P. Maurya; V. S. Chouhan; Gyanendra Singh (Tropical Animal Health and Production, 2023)

Relevance of phosphate solubilizing microbes in sustainable crop production: a review - F. Fatima; M. M. Ahmad; S. R. Verma; N. Pathak (International Journal of Environmental Science and Technology, 2022)

Feasibility of bioleaching integrated with a chemical oxidation process for improved leaching of valuable metals from refinery spent hydroprocessing catalyst - Ashish Pathak; Mohan S. Rana; Hanadi Al-Sheeha; Rajasekaran Navvmani; Hanan M. Al-Enezi; Sakeena Al-Sairafi; Jayshree Mishra (Environmental Science and Pollution Research, 2022)

Theory, methods, and operational results of the Young Women’s Health History Study: a study of young-onset breast cancer incidence in Black and White women - Ellen M. Velie; Lydia R. Marcus; Dorothy R. Pathak; Ann S. Hamilton; Ralph DiGaetano; Ron Klinger; Bibi Gollapudi; Richard Houang; Nicole Carnegie; L. Karl Olson; Amani Allen; Zhenzhen Zhang; et al. (Cancer Causes & Control, 2021)
Purpose The etiology of young-onset breast cancer (BC) is poorly understood, despite its greater likelihood of being hormone receptor-negative with a worse prognosis and persistent racial and socioeconomic inequities. We conducted a population-based case–control study of BC among young Black and White women and here discuss the theory that informed our study, exposures collected, study methods, and operational results. Methods Cases were non-Hispanic Black (NHB) and White (NHW) women age 20–49 years with invasive BC in metropolitan Detroit and Los Angeles County SEER registries 2010–2015. Controls were identified through area-based sampling from the U.S. census and frequency matched to cases on study site, race, and age. An eco-social theory of health informed life-course exposures collected from in-person interviews, including socioeconomic, reproductive, and energy balance factors. Measured anthropometry, blood (or saliva), and among cases SEER tumor characteristics and tumor tissue (from a subset of cases) were also collected. Results Of 5,309 identified potentially eligible cases, 2,720 sampled participants were screened and 1,812 completed interviews (682 NHB, 1140 NHW; response rate (RR): 60%). Of 24,612 sampled control households 18,612 were rostered, 2,716 participants were sampled and screened, and 1,381 completed interviews (665 NHB, 716 NHW; RR: 53%). Ninety-nine% of participants completed the main interview, 82% provided blood or saliva (75% blood only), and SEER tumor characteristics (including ER, PR and HER2 status) were obtained from 96% of cases. Conclusions Results from the successfully established YWHHS should expand our understanding of young-onset BC etiology overall and by tumor type and identify sources of racial and socioeconomic inequities in BC.

Incidence and Diversity of Termites Associated with Sugarcane in North-West Zone of India with New Records - S. N. Sushil; C. M. Kalleshwaraswamy; M. Ranjith; Sharmila Roy; A. K. Jaiswal; Deeksha Joshi; A. D. Pathak (Sugar Tech, 2021)

Insights of Bipolaris sorokiniana secretome - an in silico approach - Gauri M. Pathak; Gayatri S. Gurjar; Narendra Y. Kadoo (Biologia, 2020)

Foliar Spray of Synthetic Osmolytes Alleviates Terminal Heat Stress in Late-Sown Wheat - A. Roy Chowdhury; M. Ghosh; M. Lal; A. Pal; K. K. Hazra; S. Acharya; A. Chaurasiya; S. K. Pathak (International Journal of Plant Production, 2020)

Determination of Morphological and Biochemical Basis of Resistance Against Top Borer, Scirpophaga excerptalis Walker in Sugarcane - S. N. Sushil; Amaresh Chandra; Sharmila Roy; A. K. Jaiswal; M. R. Singh; A. D. Pathak (Sugar Tech, 2020)

Impact of Temperature and Humidity on Sugar Recovery in Uttar Pradesh - S. K. Pathak; Priyanka Singh; M. M. Singh; B. L. Sharma (Sugar Tech, 2019)

Understanding the role of moisture transport on the dry bias in indian monsoon simulations by CFSv2 - A. S. Sahana; Amey Pathak; M. K. Roxy; Subimal Ghosh (Climate Dynamics, 2019)

Role of government in flood disaster recovery for SMEs in Pathumthani province, Thailand - S. Pathak; M. M. Ahmad (Natural Hazards, 2018)

Satellite‐retrieved direct radiative forcing of aerosols over North‐East India and adjoining areas: climatology and impact assessment - Jhuma Biswas; Binita Pathak; Falguni Patadia; Pradip K. Bhuyan; Mukunda M. Gogoi; S. Suresh Babu (International Journal of Climatology, 2017)

Impact of High Sugar Early Maturing Varieties for Sustainable Sugar Production in SubTropical India - Priyanka Singh; S. K. Pathak; M. M. Singh; V. Mishra; B. L. Sharma (Sugar Tech, 2017)

Satellite‐retrieved direct radiative forcing of aerosols over North‐East India and adjoining areas: climatology and impact assessment - Jhuma Biswas; Binita Pathak; Falguni Patadia; Pradip K. Bhuyan; Mukunda M. Gogoi; S. Suresh Babu (International Journal of Climatology, 2017)
In order to understand the climatic implications of atmospheric aerosols, top of atmosphere ( TOA ) shortwave ( SW , 0.3–5 µm) fluxes and aerosol optical depth ( AOD ) at 550 nm retrieved simultaneously by clouds and the earth's radiant energy system ( CERES ) and moderate resolution imaging spectroradiometer ( MODIS ) instruments, respectively, are analysed over North‐East India and its adjoining areas for the period July 2002–December 2013. The aerosol‐free TOA flux obtained by establishing the linear regression between CERES SW TOA fluxes and MODIS AODs exhibits strong seasonality with peak values in monsoon and minimum in winter. Same seasonality is captured by the Santa Barbara DISORT Atmospheric Radiative Transfer ( SBDART ) model, but with difference in absolute values. SBDART code is used to extend instantaneous radiative forcing estimates into 24‐h averages. AOD over the North East India region with complex terrain shows altitudinal variation with maximum value at the lowest elevation site Dhaka and minimum value at the high‐altitude locations Shillong and Aizwal. In general, strong seasonality in AOD is observed with a peak in pre‐monsoon (March–May) and dip in post‐monsoon (October–November) at all the locations. The direct instantaneous TOA shortwave aerosol radiative forcing ( SWARF ) shows maximum values in pre‐monsoon over all the locations except at Guwahati, Banmauk, Aizawl, and Shillong. The lowest value of instantaneous SWARF is observed in post‐monsoon except at Banmauk and Shillong. Climatologically TOA diurnally averaged SWARF varies between −6.95 W m −2 in Aizawl to −20.39 W m −2 in Shillong. In general, the TOA SW forcing efficiency is highest in monsoon at all the locations. The radiative forcing efficiency is found to be less negative when surface reflectance increases.

Weed and Nitrogen Management Effects on Weed Infestation and Crop Productivity of Wheat–Mungbean Sequence in Conventional and Conservation Tillage Practices - C. P. Nath; T. K. Das; K. S. Rana; R. Bhattacharyya; H. Pathak; S. Paul; M. C. Meena; S. B. Singh (Agricultural Research, 2017)

Physicochemical and toxicological characterization of sucrose-bound polynuclear iron oxyhydroxide formulations - Bhavesh S. Barot; Punit B. Parejiya; Pragna K. Shelat; Gaurang B. Shah; Dharmik M. Mehta; Trupti V. Pathak (Journal of Pharmaceutical Investigation, 2015)

Mitigation of greenhouse gas emission with system of rice intensification in the Indo-Gangetic Plains - Niveta Jain; Rachana Dubey; D. S. Dubey; Jagpal Singh; M. Khanna; H. Pathak; Arti Bhatia (Paddy and Water Environment, 2014)

Spatial heterogeneity in near surface aerosol characteristics across the Brahmaputra valley - Binita Pathak; Arup Borgohain; Pradip Kumar Bhuyan; Shyam Sundar Kundu; S Sudhakar; Mukunda M Gogoi; Toshihiko Takemura (Journal of Earth System Science, 2014)

Particulate matter concentration in ambient air and its effects on lung functions among residents in the National Capital Region, India - C. Kesavachandran; B. S. Pangtey; V. Bihari; M. Fareed; M. K. Pathak; A. K. Srivastava; N. Mathur (Environmental Monitoring and Assessment, 2013)

Multiscale Imaging and Computational Modeling of Blood Flow in the Tumor Vasculature - Eugene Kim; Spyros Stamatelos; Jana Cebulla; Zaver M. Bhujwalla; Aleksander S. Popel; Arvind P. Pathak (Annals of Biomedical Engineering, 2012)

Variability of Albedo and Utility of the MODIS Albedo Product in Forested Wetlands - David M. Sumner; Qinglong Wu; Chandra S. Pathak (Wetlands, 2011)

Genomic mapping and testing for quantitative trait loci in tea (Camellia sinensis (L.) O. Kuntze) - S. M. Kamunya; F. N. Wachira; R. S. Pathak; R. Korir; V. Sharma; R. Kumar; P. Bhardwaj; R. Chalo; P. S. Ahuja; R. K. Sharma (Tree Genetics & Genomes, 2010)

Complete nucleotide sequence of the envelope gene of pseudocowpox virus isolates from Indian dromedaries (Camelus dromedarius) - G. Nagarajan; S. K. Ghorui; Sanjay Kumar; K. M. L. Pathak (Archives of Virology, 2010)

Isolation and characterization of Indian isolates of camel pox virus - V. Bhanuprakash; V. Balamurugan; M. Hosamani; G. Venkatesan; Bina Chauhan; V. A. Srinivasan; R. S. Chauhan; K. M. L. Pathak; Raj Kumar Singh (Tropical Animal Health and Production, 2010)

Water quality assessment of Majhiaon block of Garwa district in Jharkhand with special focus on fluoride analysis - Kirti Avishek; Gopal Pathak; M. S. Nathawat; Usha Jha; Neeta Kumari (Environmental Monitoring and Assessment, 2010)

Reproductive performance of crossbred dairy cows reared under traditional low input production system in the eastern Himalayas - A. Kumaresan; P. P. Prabhakaran; K. M. Bujarbaruah; K. A. Pathak; Bijoy Chhetri; S. K. Ahmed (Tropical Animal Health and Production, 2009)

Enhancement in alpha-tocopherol succinate-induced apoptosis by all-trans-retinoic acid in primary leukemic cells: role of antioxidant defense, Bax and c-myc - K. L. Khanduja; S. Kumar; N. Varma; S. C. Varma; P. K. Avti; C. M. Pathak (Molecular and Cellular Biochemistry, 2008)

Analysis of a village chicken production system and performance of improved dual purpose chickens under a subtropical hill agro-ecosystem in India - A. Kumaresan; K. M. Bujarbaruah; K. A. Pathak; Bijoy Chhetri; S. K. Ahmed; Santosh Haunshi (Tropical Animal Health and Production, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Isolation and characterization of mutants of Pseudomonas maltophila PM-4 altered in chitinolytic activity and antagonistic activity against root rot pathogens of clusterbean (Cyamopsis tetragonoloba) - E. Yadav; D. V. Pathak; S. K. Sharma; M. Kumar; P. K. Sharma (Indian Journal of Microbiology, 2007)

Subtractive differential display: a modified differential display technique for isolating differentially expressed genes - Rashmi U. Pathak; M. S. Kanungo (Molecular Biology Reports, 2007)

Soil Properties and Crop Productivity as Influenced by Flyash Incorporation in Soil - Naveen Kalra; M. C. Jain; H. C. Joshi; R. Chaudhary; Sushil Kumar; H. Pathak; S. K. Sharma; Vinod Kumar; Ravindra Kumar; R. C. Harit; S. A. Khan; M. Z. Hussain (Environmental Monitoring and Assessment, 2003)

Emission of Nitrous Oxide from Rice-Wheat Systems of Indo-Gangetic Plains of India - H. Pathak; Arti Bhatia; Shiv Prasad; Shalini Singh; S. Kumar; M. C. Jain; U. Kumar (Environmental Monitoring and Assessment, 2002)

Long-term changes in yield and soil fertility in a twenty-year rice-wheat experiment in Nepal - Gami S.; Ladha J.; Pathak H.; Shah M.; Pasuquin E.; Pandey S.; Hobbs P.; Joshy D.; Mishra R. (Biology and Fertility of Soils, 2001)

Mitigation of N 2 O emission from an alluvial soil by application of karanjin - Majumdar D.; Dutta A.; Kumar S.; Pathak H.; Jain M. (Biology and Fertility of Soils, 2001)

Nitrous oxide emission from different fertilizers and its mitigation by nitrification inhibitors in irrigated rice - U. Kumar; M. C. Jain; H. Pathak; S. Kumar; D. Majumdar (Biology and Fertility of Soils, 2000)

Thyroid functions in lithium-treated psychiatric patients - S. D. Deodhar; B. Singh; C. M. Pathak; P. Sharan; P. Kulhara (Biological Trace Element Research, 1999)

The Imperata grasslands of tropical Asia: area, distribution, and typology - D. P. Garrity; M. Soekardi; M. van Noordwijk; R. de la Cruz; P. S. Pathak; H. P. M. Gunasena; N. van So; G. Huijun; N. M. Majid (Agroforestry Systems, 1996)